Temporal aggregation in political budget cycles - Jorge M. Streb; Daniel Lema (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2009)
While existing cross-country studies on political budget cycles rely on annual data, we build a panel with quarterly and monthly data from Latin American and OECD countries over the 1980-2005 period. Disaggregated data allow to center the electoral year more precisely, and show the effects are concentrated in a three-quarter window around elections. Cycles are statistically significant only in Latin America, but the pattern is similar to OECD countries: the budget surplus/GDP ratio falls in the election period and rises in the post-election period. In line with the logic of rational opportunistic manipulation, these effects cancel out.
Keywords: D72; D78; H60; 330; temporal aggregation; electoral window; pre- and post-electoral effects; political budget cycles; rational opportunistic cycles